PEMANFAATAN APLIKASI PHOTOMARH SEBAGAI MEDIA PEMBELAJARAN UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA PADA MATERI PERSAMAAN LINEAR SATU VARIABEL - Ulfah, Maria; Puspitasari, Yesi; Surur, Miftahus (Yayasan Amanah Nur Aman, 2025)
The development of technology and communication provides ideas or solutions to educators to utilize developing technology to find media or learning methods that can be applied or taught to students which aim to facilitate students in learning and solving problems related to problems that they find difficult to solve, especially in solving problems related to mathematics learning. The research objectives to be achieved in this study are to determine the utilization of the photomarh application as a learning medium to increase student learning motivation in the material of linear equations of one variable class. The research method is the approach and type of research using qualitative methods with a descriptive approach. The technique of selecting research subjects using purposive method, namely all VIII grade students. From the results of the research conducted, it can be seen that the utilization of the photomarh application is very helpful in learning which can be seen from the evaluation of learning. The utilization of the application is also very much in accordance with mathematics learning, one of which is linear equations of one variable. The utilization of the photomarh application is to facilitate students in the learning process so as to improve student learning outcomes. The utilization of digital applications, namely the photomarh application, is very suitable for the material in mathematics learning, namely the material for linear equations of one variable.